A comparison of water photo-oxidation and photo-reduction using photoelectrodes surface-modified by deposition of co-catalysts: Insights from photo-electrochemical impedance spectroscopy. (19th April 2019) - Antuch, M.; El Rouby, W.M.A.; Millet, P.
Abstract: The purpose of this research paper is to highlight the similarities in the kinetic treatment between water photo-oxidation into molecular oxygen and water photo-reduction into molecular hydrogen, using photoelectrodes surface modified by deposition of co-catalysts. Photo-anodes made of TiO2 nanorods surface-covered by crystals of cobalt Zeolitic Imidazolate Framework (ZIF-67), and photo-cathodes made of Rh:SrTiO3 particles surface-modified by adsorption of molecules of trisdioximate hexa-chlorine cobalt (II) clathrochelate (Co(Cl2 Gm)3 (BCH3 )2 ), have been prepared and used for water photo-oxidation and photo-reduction experiments, respectively. Both photoelectrodes have been characterized by SEM and cyclic voltammetry under illumination conditions. Charge transfer mechanisms have been investigated by photo-electrochemical impedance spectroscopy (PEIS). It is shown that for both systems, the presence of a co-catalyst increases the charge transfer kinetics, and that the trapping resistance is larger than the charge transfer resistance, at any operating potential. Highlights: Water photo-oxidation on titanium dioxide with Zeolitic Imidazolate Framework. Water photo-reduction on strontium titanate with cobalt clathrochelate. The mechanisms are analyzed by photo-electrochemical impedance spectroscopy. Data are modeled by taking into account surface trapping of charge carriers. Microscopic rate parameters of the two systems are compared.